Methods for Including Adverse Events in Economic Evaluations: Suggestions for Improvement - Ghabri, Salah; Dawoud, Dalia; Drummond, Michael (Value in health, 2024)
Inclusion of relevant effectiveness and safety outcomes in economic evaluation of health technologies is required to aid efficient healthcare decisions. Our objective was to identify the key issues related to the inclusion of adverse events (AEs) in economic evaluation and explore perspectives for good practice recommendations to handle these issues. We focused on the frequently encountered methodological issues related to the integration of AEs in economic evaluations of health technologies. We distinguished the following elements: the incorporation of AEs in decision models, the terminology of AEs, the estimation of AEs consequences in terms of quality of life (QoL) and costs, and the exploration of the uncertainty related to the impact of AEs on the economic results. We illustrated and discussed each of the identified issues by giving health technology assessment examples. We focused on the extent to which the integration of AEs in decision models can be improved by dealing with the lack of relevant real-world safety data, estimating the consequences of AEs (eg, for costs and QoL loss), exploring the impacts of AEs that are not adequately captured in current measurement of health-related QoL, and identifying the need for development of a good terminology of relevant types of AEs to be incorporated in economic evaluation. Based on a reflection the key methodological issues related to the incorporation of adverse drug events in economic evaluations, we suggested several recommendations to serve a starting point for health technology assessment agencies and researchers to develop good research practices in this field. •Today, there are no standardized methods related to the inclusion of adverse events (AEs) in economic evaluations of health technologies. The current health technology assessment guidelines of health technologies illustrate an unmet need for improving methods for including AEs in economic evaluations.•Good research practices on improving the integration of AEs in economic evaluation are necessary and should explore specific health technology assessment recommendations (eg, decision analytic models, terminology and types of AEs, the estimation of their impacts in terms of quality of life and costs, and uncertainty).